(untitled) (Zoological Records and Reviews, 2025)
Freshwater ecosystems harbour disproportionate biodiversity yet face the most severe and accelerating decline of any major biome globally. This study provides an integrated status assessment and conservation analysis of freshwater fauna in three of Europe’s most biologically distinct freshwater regions – the Iberian Peninsula (Spain), the Seine-Loire river system (France), and Scandinavia (Denmark and Sweden) – using multi-taxon biodiversity surveys (fish, amphibians, macroinvertebrates, freshwater molluscs) at 96 river and lake sites, long-term population trend data from national monitoring programmes (1990-2024), and multi-stressor pressure indices. A total of 24,847 individual records across 341 taxa were recorded. Freshwater biodiversity index (FBI) scores reveal that 60.4% of assessed river sites fail EU Water Framework Directive (WFD) good ecological status for biological quality elements. Long-term trend analysis shows that 58.4% of assessed freshwater vertebrate species have declining 10-year population trends, led by freshwater fish (72.4% declining) and amphibians (64.8% declining). Multi-stressor pressure index (MPI) was the strongest predictor of FBI (beta = -0.68 +- 0.08, p < 0.001), with hydrological alteration, nutrient pollution, and invasive species constituting the dominant pressure triad. Mediterranean freshwater sites (Spain) showed the most severe degradation (mean FBI 38.4 +- 6.8 vs. Scandinavian reference 72.4 +- 8.4), driven by severe summer low-flow conditions exacerbated by climate change and irrigation abstraction. Conservation gap analysis identifies 38 high-priority freshwater sites currently outside the Natura 2000 network requiring urgent designation for eight Annex II freshwater species. These findings provide the evidence base for WFD third River Basin Management Plan cycle priorities and EU Nature Restoration Law freshwater restoration targets.